2012
DOI: 10.2337/dc11-1109
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Safety of Long-Term Fenofibrate Therapy in People With Type 2 Diabetes and Renal Impairment

Abstract: OBJECTIVEDiabetic patients with moderate renal impairment (estimated glomerular filtration rate [eGFR] 30–59 mL/min/1.73 m2) are at particular cardiovascular risk. Fenofibrate’s safety in these patients is an issue because it may elevate plasma creatinine. Furthermore, guidelines regarding fenofibrate dosing in renal impairment vary internationally. We investigated fenofibrate’s effects on cardiovascular and end-stage renal disease (ESRD) events, according to eGFR, in the Fenofibrate Intervention and Event Low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 30 publications
4
83
0
2
Order By: Relevance
“…While patients in the placebo group of this study with moderate renal impairment had the highest cardiovascular event rates, fenofibrate treatment was associated with a relative reduction in cardiovascular risk of 32% versus 15% in patients with normal renal function [53]. Admittedly, this analysis was based on a limited sample (~5% of the total study population), and the use of the Modification of Diet in Renal Disease formula in FIELD may have underestimated eGFR.…”
Section: Reducing Residual Microvascular Riskmentioning
confidence: 98%
“…While patients in the placebo group of this study with moderate renal impairment had the highest cardiovascular event rates, fenofibrate treatment was associated with a relative reduction in cardiovascular risk of 32% versus 15% in patients with normal renal function [53]. Admittedly, this analysis was based on a limited sample (~5% of the total study population), and the use of the Modification of Diet in Renal Disease formula in FIELD may have underestimated eGFR.…”
Section: Reducing Residual Microvascular Riskmentioning
confidence: 98%
“…W badaniu wykazano również możliwość korzystnego efektu terapii skojarzonej w postaci redukcji o 30% incydentów sercowo-naczyniowych u osób z równoczesnym wysokim stężeniem TG (≥ 204 mg/dl) i niskim stężeniem HDL-C (≤ 34 mg/dl). W żadnym z wymienionych badań przejściowy wzrost stężenia kreatyniny w surowicy krwi nie skutkował działaniami niepożądanymi w zakresie poważnych zdarzeń nerkowych, co sugeruje możliwe korzyści przy długotrwałej terapii [38][39][40][41][42].…”
Section: Fibraty W Nefrologiiunclassified
“…The investigators concluded that fenofibrate should be considered as an additional therapeutic option, along with conventional risk-factor management, to further reduce CVD events and m ortality and provide renoprotection to patients with diabetes, as well as to those with moderate renal impairment. 8 9 the addition of fenofibrate (160 mg daily) to simvastatin treatment (10-40 mg daily) was assessed in 5,518 participants with diabetes. No significant difference was found in the primary outcome of nonfatal myocardial infarction, nonfatal stroke, or cardiovascular death.…”
Section: Correspondencementioning
confidence: 99%